Application of thermal energy storage materials for solar cooking : a comprehensive review - Patel, Romil; Patel, Vikram (Penerbit Universiti Kebangsaan Malaysia, 2022)
Food, cloth and shelter are three basic necessities of life. Food can be regarded as essential component for growth and survival of human being. So, the source of cooking is one of the most important things in our daily lives. There are various cooking sources of energy like kerosene, LPG, Firewood and Renewable sources etc. and one of them is solar cooking which is a renewable source of energy. Solar cooks are limited by the fact that cooking can only take place during daytime. If a thermal energy storage system is provided to solar cookers, food can be cooked during hours of evening or night. In the last few decades, the cooking sector has used various solar cookers, including the box type solar cooker, flat plate type solar cooker, parabolic dish type solar cooker, evacuated tube type solar cooker and Scheffler dish solar cooker with sensible heat, latent heat and Combined heat storage technologies for the solar cooker. As a result, this paper summarizes the investigation and analysis of the available thermal energy storage materials (sensible heat, latent heat and combined heat storage materials) to store heat during the daytime and use it for purposes other than daytime hours for use in solar cooking application. The current study also compares the Sensible heat, Latent heat and combined heat storage systems for cooking.